If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+5x+3+7=6x+4+3x
We move all terms to the left:
5x+5x+3+7-(6x+4+3x)=0
We add all the numbers together, and all the variables
5x+5x-(9x+4)+3+7=0
We add all the numbers together, and all the variables
10x-(9x+4)+10=0
We get rid of parentheses
10x-9x-4+10=0
We add all the numbers together, and all the variables
x+6=0
We move all terms containing x to the left, all other terms to the right
x=-6
| (3,0.5);b=1.5 | | 2/3x=7/15 | | 12-(4x-7)-33=8(7x+1) | | Y=2x(4)+3 | | -2-2/3x=10 | | 63w+11w=52w+121 | | 4x+4=3x1 | | 50x-5x+3x=2385000 | | 2/3(k-3)=2/3(2k+1) | | X^4-122x^2+121=0 | | 3t+1-8=-3 | | 28-(n-2)=5(n+5) | | x-x/3=7/15 | | 6(x-2)=7x+14 | | 10-3(m+6)=8 | | F(-5)=3x^2+2x-2 | | 55=15^x | | 0=20x-44-2x^2 | | 11y+39=72 | | 44=-7x+4x+8 | | 15-3(x+8)-15=-3 | | 2/3q-7=8 | | 20-3(m-2)=8 | | 7h+3=11 | | 11x+-3=30 | | 3(x-4)-2(x-5)=6+2(x+1)+3x | | Y=20x-44-2x^2 | | -12x+6=-10x-4 | | 2(h+6)-10=4 | | 1=w/136+0.3 | | -3x=143+8x | | -10=5x+7x-10 |